Clinico-pathological evaluation of cervical lymphadenopathy - Mukhia, Rupesh; Bhatta, Sushama; Simkhada, Ganesh; Thapa, Abishek; Mukhia, Rupashia (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Cervical lymph nodes are peripheral lymphoid organs distributed in the neck. The term lymphadenopathy refers to nodes that are palpable and abnormal in size, consistency or numbers. Diagnosis of cervical lymphadenopathy can vary from neoplasm to various kinds of infection. Accurate diagnosis of the cause of lymphadenopathy can sometimes be challenging and can lead to delay in diagnosis causing delayed treatment and subsequent health issues. Methods: A prospective observational study was carried out on 78 patients of cervical lymphadenopathy who presented in the surgical outpatient department of KIST Medical College. Detailed history, physical examination and necessary investigations including fine needle aspiration cytology were done in all patients Results: Most patients were between 21 to 40 years of age. The commonest cause for cervical lymphadenopathy was reactive lymphadenitis (53.84%) followed by Tuberculosis (34.61%). Secondary metastasis was seen in 7 patients (8.97%). In tubercular lymphadenitis, the anterior triangle group was the most commonly involved group of cervical lymph nodes (74 %), followed by the posterior triangle and supraclavicular equally (11.11%). Conclusions: Reactive Lymphadenopathy is the commonest cause of cervical lymphadenopathy. However, variable diagnosis can be possible from non-neoplastic to neoplastic condition.